2017
DOI: 10.15226/jnhfs.2017.00188
|View full text |Cite
|
Sign up to set email alerts
|

Legumes Consumption among Young and Adult Residents In Sicily (South Italy): Evidence and Predictive Factors

Abstract: [3]. Humans have observed, over many centuries, that diets low in meat and high in cereals and legumes are beneficial for health. Epidemiological studies over the last 20 years have conformed these observations i.e that eating legumes can extend life by preventing chronic disease, including cardiovascular disease, coronary artery disease [4], diabetes, bowel cancer [5] and overweight as well as improving gut health [6,7,8]. The consumption of legumes is recommended by public health agencies around the world. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 15 publications
1
2
0
1
Order By: Relevance
“…Our results indicate that the frequency of legumes consumption (3-6 times/week) is satisfactory to the dietary guidelines for middle eastern countries (62). Moreover, our results are similar to previously reported studies in Jordan (63) and Greece (64), where legume consumption was shown to be 3-4 times per week, and more frequent than other Mediterranean countries such as Spain and Italy (once per week) (65,66). This signifies a preservation of legume consumption in Lebanon although the concomitant tendency to shift to more westernized diets (42).…”
Section: Main Sources Of Dietary Ironsupporting
confidence: 90%
“…Our results indicate that the frequency of legumes consumption (3-6 times/week) is satisfactory to the dietary guidelines for middle eastern countries (62). Moreover, our results are similar to previously reported studies in Jordan (63) and Greece (64), where legume consumption was shown to be 3-4 times per week, and more frequent than other Mediterranean countries such as Spain and Italy (once per week) (65,66). This signifies a preservation of legume consumption in Lebanon although the concomitant tendency to shift to more westernized diets (42).…”
Section: Main Sources Of Dietary Ironsupporting
confidence: 90%
“…It was observed that each of the pulse species and products, as well as whole group, may entail different consumer perception and result in different levels of intake. A study from South Italy showed that women were more frequent pulse eaters; however, in our sample gender did not contribute to significant differences between profiles [ 40 ]. Although differences were not very significant, we observed that lentils and chickpeas were more popular among younger consumers (25–34 years) and living in the biggest Polish cities.…”
Section: Discussionmentioning
confidence: 66%
“…This study provided data about attitudes, incentives and barriers to pulse consumption among consumers aged 25–40 years and living and working in Polish cities. Other authors found that higher consumption of pulses was reported among younger, highly educated adults living in big cities [ 38 , 39 , 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Co piąty badany jada te rośliny często lub bardzo często (Rysunek 2). Source: own research Znacznie wyższe spożycie tej grupy roślin stwierdzono w badaniach przeprowadzonych we Włoszech, gdzie 42,4% ankietowanych, w tym 38,5% studentów, spożywało rośliny strączkowe przynajmniej raz w tygodniu [21]. W badaniach wśród polskich studentów, większość respondentów deklarowała, że spożywa nasiona roślin strączkowych rzadziej niż raz w miesiącu (44,8%) lub kilka razy w miesiącu (43,8%).…”
Section: Wyniki I Ich Omówienieunclassified